Design and Construction of Duku Sorting System Based on Size Using a Microcontroller on Conveyor Work - Martinus, Martinus; Muhammad, Meizano Ardhi; Telaumbanua, Mareli; Andrianto, Rifqi Rhama; Ferbangkara, Sony (International Journal of Electronics and Communications Systems, 2021)
Duku (Lansuim Domesticum Corr)fruit harvesting is generally done manually by farmers in Indonesia so that the quality of the duku fruit, especially the uniformity of size, is not considered. The impact of this harvesting is a decrease in fruit quality and a decrease in selling prices. It is necessary to develop a new sorting machine for duku so that the fruit size is accurate. This research aims to make a sorting system for duku fruit based on size using a microcontroller on conveyor work. The sorting system uses two sensors, VL53L0X and FC-51. The design has a servo actuator to separate the fruit classes. This study developed a correct sorting of duku fruit sizes up to 97.4 percent, counting accuracy up to 99.4 percent, system stability up to 96.65 percent, and transient response of 100 ms. The result of testing this tool is that the ability of the Duku fruit sorting system based on size has a stability value of 96.6 percent. The transient response obtained is 100ms. The accuracy of the perfect sorting results is 97.4 percent, and the calculation of the number of duku using the system is 99.4 percent. The conclusion is that the researchers can create a sorting system based on size using a microcontroller on conveyor work.